A year later, Flint still can't drink the water. - Sanburn, Josh
For the residents of Flint, Michigan, the burden of ongoing water crisis can be measured in weight. For more than a year, many Flint residents have been making the daily journey to distribution centers to load up on cases of water for virtually every basic chore: bathing, brushing teeth, and making dinner. Twelve months after a state of emergency was declared to deal with the catastrophic decision to switch the municipal water supply to the Flint River, which allowed lead and other toxins from the city's aging pipes to flow into residents' taps, the water in Flint remains unsafe to drink without a filter--this despite millions in aid pledged by Congress, and more millions from the state and a concerted grassroots effort. But there are halting signs of progress. Here, Sanburn offers a look at the progress made in the city's water supply one year after the crisis.
Keywords: Water quality; Water-supply.